Promotion and diffusion of tha career Bachelor and Licenciature of Mathematics Teaching in rural areas of Costa Rica project: effects and results - Arroyo Hernández, Jorge (2012)
This article describes the purpose and activities of the project Promoting Mathematics Education in Rural Areas of Costa Rica. The activity has focused on two objectives. First, supporting and monitoring students who have expressed interest in studying a mathematics teacher. To achieve this, it has been working with students who have an ideal profile for the career, mainly from rural areas. The second objective is to conduct training workshops for high school in-service teachers, to strengthen and improve their knowledge in the area of mathematics. Among the results of the project, it can be highlighted a significant increase in the enrollment of students in the career of Mathematics Education in 2010 and 2011, and the training processes in the field of Real Functions of Real Variable and Geometry at different regional areas mostly rural as Aguirre, Sarapiquí, Coto, Buenos Aires, Limón, Cañas, Pérez Zeledón, Nicoya, Los Santos, Turrialba, Puriscal, Desamparados, San Carlos, Puntarenas, Limón, Liberia, Santa Cruz y Upala.